Experimental Analysis of Vertical Vibrations of a Railway Bogie - Mădălina Dumitriu; Ioan Cristian Cruceanu (Communications - Scientific letters of the University of Zilina, 2021)
The paper presents a study of the vertical vibrations of a bogie of a passenger vehicle, based on the acceleration of the axles and the bogie frames, measured during the running at a constant velocity. To this purpose, the root mean square (RMS) acceleration is calculated for more measurement sequences at different velocities. In principle, the RMS acceleration increases along with the velocity and influence of the variability of the amplitude in the track defects upon the dispersion of the values in the RMS acceleration. Based on the spectral analysis of the measured acceleration, wheel defects and undulatory wear of the rolling surfaces of wheels and rail are highlighted.